1978
DOI: 10.1111/j.1365-2311.1978.tb00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the ovaries of olive flies (Dacus oleae (Gmelin)) during the summer, and their relationship to temperature, humidity and fruit availability

Abstract: Abstract. 1. Examination of the ovaries of female olive flies (Dacus oleae) from wild populations on Corfu during the summer months of 1975 indicated that all were non‐gravid for a period of several weeks during June and July and the terminal follicles were resorbed. 2. Experiments in outdoor cages indicated that olive fruits could stimulate ovarian development during the summer months. 3. Experiments in constant temperature cabinets indicated that high temperatures (i. e. 26–29°C) in conjunction with a low h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
2
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 2 publications
3
88
2
4
Order By: Relevance
“…Furthermore, although there were eggs in the agar, the total number of eggs in the pairings in which the agar was present was smaller than in other pairings. Hosts of low nutritional quality for larvae seem to reduce egg production in several species of insects (Fletcher et al 1978). Aluja et al (2001) observed that the presence of hosts and their volatile substances are important for ovarian maturation of A. obliqua.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although there were eggs in the agar, the total number of eggs in the pairings in which the agar was present was smaller than in other pairings. Hosts of low nutritional quality for larvae seem to reduce egg production in several species of insects (Fletcher et al 1978). Aluja et al (2001) observed that the presence of hosts and their volatile substances are important for ovarian maturation of A. obliqua.…”
Section: Discussionmentioning
confidence: 99%
“…An absence of mature eggs in fly ovaries during the spring and early summer has often been noted in European B. oleae populations (Delrio and Prota 1976;Economopoulos et al 1982;Fletcher et al 1978;Raspi et al 2002;Tzanakakis 1986) and is referred to as a summer reproductive diapause. A similar absence of mature eggs can be induced in flies reared in the laboratory by exposing larvae to cool, short days and adults to hot, long days with no access to olives Tzanakakis 1990, 1993;Koveos et al 1997;Raspi et al 2002;Raspi et al 2005).…”
Section: Reproductive Biologymentioning
confidence: 99%
“…This observation may have reflected that egg and larval fruit flies experience high mortality during hot, dry weather (Kapatos and Fletcher 1984). There may have been an effect of reproductive diapause, which may be prolonged under hot and dry conditions even when ripe olive fruit are present (Fletcher et al 1978). We might therefore expect dramatic differences in population dynamics in the various olive production areas in California, such as in cool, coastal San Luis Obispo County versus relatively hot, inland Tulare County.…”
Section: Biology Life Cycle and Populationmentioning
confidence: 99%
“…The most detailed information about olive fruit fly population ecology comes from a series of studies in an unsprayed olive grove in Corfu, Greece (Fletcher et al 1978;Fletcher and Kapatos 1981;Kapatos and Fletcher 1984). Olive fruit fly dynamics are likely to be similar in California, although this remains to be determined.…”
Section: Biology Life Cycle and Populationmentioning
confidence: 99%
See 1 more Smart Citation